Für Israel und die Völker : Studien zum alttestamentlich-jüdischen Hintergrund der paulinischen Theologie - Oegema, Gerbern S., 1958- (Novum Testamentum, Supplements, 1999)
In this work, the author investigates Gal 1:13-14, Gal 3:6-14, 1 Thess 4:13-17, 2 Cor 12:1-10 and Rom 10:4 and then expounds how Paul, although originating from Judaism and having been educated in Jewish Biblical interpretation, reaches a new hermeneutic only after his experience of Christ. The apostle proves to be dependent neither on apocalyptic views nor on the methods of Greek Rhetoric nor on Rabbinic Midrash, although he is well versed in them. Instead, he develops a Christological interpretation of the Torah, and this interpretation becomes the centre of his mission to the non-Jews. The Torah finds its eschatological fulfillment in Christ and receives its ethical validity for the nations in the form of the love command.